Faktor yang Mempengaruhi Penawaran Output pada Industri Pisang Aroma KPK Mawar di Desa Gesing Kecamatan Kandangan Kabupaten Temanggung - Antik Suprihanti; Siti Hamidah; Sayekti Sayekti (Jurnal Dinamika Sosial Ekonomi, 2009)
SAYEKTI The Factory That Influence Oput Supply of "Aroma" banana at "KPK Mawar" industry in Gesing Village, Kandangan sub district, Temanggung Regency. Supervised by This research aim to 1). Analyze the factor that influence output apply of "Aroma" Banana at "KPK Mawar" Industry 2). Know the constraint that faced by "KPK Mawar" Industry.  The method that used is case study method Location determination method performed purposively, the kind of data are primary data and secondary data, data source are "Aroma" banana KPK Mawar Industry related stine and literature books. The data collection by observation interview and recording Analysis result show the factor that influence to output supply of troma banana "KPK Mawar industry are banana price and Aroma banana price While the constraint thar faced are capital limitedness, the increase of raw maerial transportation, and production tools. The most prices important constraint is capital limitedness.Keyword: Output supply, Input supply, Output prices